Answer:
The solution for x and y in (2x - 1) + (3y + 2)i = 5 – 4i cannot be determined.
Solution:
From question, the equation given is
(2x - 1) + (3y + 2)i = 5 – 4i
Multiplying the terms inside the bracket (3y + 2) with i, the above equation becomes,
(2x – 1) + 3iy + 2i = 5 – 4i
Removing the parenthesis in (2x – 1), the above equation becomes,
2x -1 + 3iy + 2i = 5 - 4i
2x – 1 + 3iy + 2i – 5 + 4i = 0
Rearranging the terms, the above equation becomes
2x + 3iy + 4i + 2i -1 -5 = 0
2x + 3iy + 6i – 6 = 0
The above equation cannot be simplified further. Hence the solution for x and y cannot be determined.